Mediated Compassion: The Role of Influencers and Digital Celebrities in Promoting a Culture of Philanthropy in Indonesia - Muhammad Deni Putra; Aliyu Bello Ahmad; Sirajuddin Shaikh (Asian Journal of Media and Culture, 2026)
The digital era has transformed philanthropic practices, shifting them onto social media platforms where visibility and performance intersect with traditional values of sincerity. This study aims to analyze the role of influencers and digital celebrities in mediating compassion and shaping a new philanthropic culture in Indonesia. Using a qualitative literature study approach, this research examines scholarly works, reports, and digital campaigns related to philanthropy on platforms like Instagram, TikTok, and YouTube. Findings indicate that influencers act as “new moral actors” who expand the reach of philanthropy but also create tensions between sincerity and digital performativity. Digital media serves as both a communication channel and a cultural arena where religious and social values are negotiated. This study concludes that the success of digital philanthropy depends not on virality alone, but on its ability to deepen social solidarity and ethical awareness, requiring a balance between technological logic and humanistic values.